2019
DOI: 10.1371/journal.pone.0217769
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of gentamicin released from collagen sponge in eradication of bacterial biofilm preformed on hydroxyapatite surface

Abstract: Biofilm-related infections of bones pose a significant therapeutic issue. In this article we present in vitro results of the efficacy of gentamicin released from a collagen sponge carrier against Staphylococcus aureus , Pseudomonas aeruginosa and Klebsiella pneumoniae biofilms preformed on hydroxyapatite surface. The results indicate that high local concentrations of gentamicin released from a sponge eradicate the biofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
0
18
1
Order By: Relevance
“…Moreover, the concentrations of antibiotic able to eradicate microbial biofilms are relatively high. Maczynska et al [ 35 ] indicated that high local concentrations of gentamicin released from collagen sponge eradicated the biofilm formed not only by gentamicin-sensitive strains but, to some extent, also by these that display a resistance pattern in routine diagnostics. Nevertheless, values of effective concentrations of gentamycin were in aforementioned Maczynska’s work above 100 mg/L in case of P. aeruginosa and S. aureus biofilm and above 700 mg/L in case of Klebsiella pneumoniae .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the concentrations of antibiotic able to eradicate microbial biofilms are relatively high. Maczynska et al [ 35 ] indicated that high local concentrations of gentamicin released from collagen sponge eradicated the biofilm formed not only by gentamicin-sensitive strains but, to some extent, also by these that display a resistance pattern in routine diagnostics. Nevertheless, values of effective concentrations of gentamycin were in aforementioned Maczynska’s work above 100 mg/L in case of P. aeruginosa and S. aureus biofilm and above 700 mg/L in case of Klebsiella pneumoniae .…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of the preliminary character and limitations of our in vitro study and we are fully conscious of the fact that our data represents first (but necessary to take) step in the research algorithm starting from in vitro results, going through the animal model study and ending in trials on patients. We hypothesize that, in the future, selected components (active substances) of EOs may be chemisorbed within organic, non-cytotoxic carrier and applied for the local treatment of osteomyelitis, as it is presently performed in the case of gentamycin-saturated collagen sponge [ 73 ]. The specific EOs’ volatile fractions may be also applied, to reach biofilm hidden within wound pockets.…”
Section: Discussionmentioning
confidence: 99%
“…Sponges for local and rapid treatment of osteomyelitis appears to be a growing area of interest, particularly in military applications, as they are readily available to pack into traumatic wounds and rapidly deliver therapeutics directly to the site of infection. 29 Reported materials of sponges include chitosan, chitosan-polycaprolactone blends, and collagen, which have been used to deliver gentamicin, 116,152 ciprofloxacin, 29,153 amikacin, 154,155 vancomycin, [154][155][156] rifampin, 29 and others. 157 In two comparative studies in humans, gentamicin loaded collagen sponges matched the efficacy of traditionally used PMMA beads in osteomyelitis treatment, while reducing the need for secondary surgical procedures.…”
Section: Spongesmentioning
confidence: 99%